2003
DOI: 10.1242/jcs.00354
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-dependent redistribution of the type-1 inositol 1,4,5-trisphosphate receptor in A7r5 smooth muscle cells

Abstract: IntroductionCellular activation by many agonists results in the stimulation of phospholipase C (PLC) and the subsequent hydrolysis of phosphatidylinositol 4,5-bisphosphate to inositol 1,4,5-trisphosphate (IP 3) and diacylglycerol (DAG) (Berridge, 1993). Each of these two molecules exerts a specific effect in the cell. The increased DAG concentration leads to the activation of protein kinase C (PKC) while IP3 binds to the IP3 receptor (IP3R), an intracellular Ca 2+ -release channel located in the endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
2
31
0
1
Order By: Relevance
“…It remains to be determined whether this model of perinuclear Ca 2+ release is involved in regulating gene transcription and other nuclear activities in other cell types. However, there are numerous studies that have examined InsP 3 R distribution in various cell types and shown that these Ca 2+ channels are often most densely concentrated around the nucleus (Bootman et al, 2001;Shirakawa and Miyazaki, 1996;Thomas et al, 2000a;Vermassen et al, 2003). It therefore seems probable that modulation of nucleoplasmic Ca 2+ concentration by perinuclear Ca 2+ release is a generic signalling paradigm.…”
Section: Measuring Nuclear Ca 2+ Signals: Key Considerationsmentioning
confidence: 99%
“…It remains to be determined whether this model of perinuclear Ca 2+ release is involved in regulating gene transcription and other nuclear activities in other cell types. However, there are numerous studies that have examined InsP 3 R distribution in various cell types and shown that these Ca 2+ channels are often most densely concentrated around the nucleus (Bootman et al, 2001;Shirakawa and Miyazaki, 1996;Thomas et al, 2000a;Vermassen et al, 2003). It therefore seems probable that modulation of nucleoplasmic Ca 2+ concentration by perinuclear Ca 2+ release is a generic signalling paradigm.…”
Section: Measuring Nuclear Ca 2+ Signals: Key Considerationsmentioning
confidence: 99%
“…Ins(1,4,5)P 3 -evoked inotropy and arrhythmias use the membrane-permeant Ins(1,4,5)P 3 ester first introduced by Tsien and colleagues (Li et al, 1997). We (Chen et al, 2004;Kasri et al, 2004;Mackenzie et al, 2002;Peppiatt et al, 2003) and several other groups (Johenning et al, 2002;Tovey et al, 2003;Vermassen et al, 2003) have used the Ins(1,4,5)P 3 ester to specifically activate Ins(1,4,5)P 3 R-mediated Ca 2+ release. All reported effects of Ins(1,4,5)P 3 ester are consistent with a sole action of the compound on Ins(1,4,5)P 3 Rs.…”
Section: Characterisation Of Sctsmentioning
confidence: 99%
“…Rather recently, evidence has been accumulating that the subcellular localization of IP 3 R is tightly controlled and changes according to circumstances (2)(3)(4). In addition, IP 3 R is known to form large clusters on the ER (5).…”
mentioning
confidence: 99%